CHARACTERISTICS OF COMSUMPTION OF PSYCHOTROPIC DRUGS AMONG STUDENTS OF HEALTH SCIENCES - MARTÍNEZ D., Gloria I.; MARTÍNEZ S., Lina M.; RODRÍGUEZ G., María de los Ángeles; MESA M., Paula A.; MUÑOZ M., Juan E.; BEDOYA M., Julián (Vitae, 2009)
Current Statistics report that psychotropic drugs consumption is increasing among young people and this is related to social and demographic factors such as age and gender, and also to psychosocial factors as friends influence and personal relations inside the family. The aim of this study is to determine social and demographic characteristics as well as prevalence and patterns of psychotropic drugs use among students of health sciences- medicine and nursery-. Pharmacological groups, the most used drugs, prevalence, frequency, and person who motivates psychotropic drugs consumption are also investigated. A crosssectional study was carried out with 820 students queried, 71.7% are female, and the group average age is 21.1 years. Prevalence use of psychotropic drugs is 18.3% for nursery and 16.5% for medicine, but this difference is not statistically significant, and it is greater in men (19%) than in women (10%), p=0.02. The findings of this study confirm the world tendency of high psychotropic drugs consumption among young people, where antidepressants appear in the first place (12.9%) independent if the consumption comes of medical prescription or self-medication.